Association of acetaldehyde dehydrogenase 2 rs671 polymorphism with the occurrence and progression of atrial fibrillation - Ge, Junye; Han, Wenqiang; Ma, Chuanzhen; Chen, Tongshuai; Liu, Huiyu; Maduray, Kellina; Qu, Yinan; Li, Yihan; Hu, Tong; Wang, Qinhong; Zhong, Jingquan (Frontiers in Cardiovascular Medicine, 2022)
Background: Acetaldehyde dehydrogenase 2 (ALDH2) is an essential enzyme in alcohol metabolism, playing a vital function in resisting oxidative stress. Lots of gene variants have been associated with atrial fibrillation (AF), among which the association between ALDH2 rs671 polymorphism and AF is variable. This study aimed to investigate the relationship between ALDH2 rs671 polymorphism and AF occurrence or progression and AF recurrence after catheter ablation. Methods: A total of 924 subjects were enrolled in the study. The ALDH2 genotypes are composed of wild-type homozygotes (ALDH2*1/*1), heterozygotes (ALDH2*1/*2), and mutant homozygotes (ALDH2*2/*2), in which the genotypes ALDH2*1/*2 and ALDH2*2/*2 are combined into the ALDH2*2. Univariate and multivariate logistic regression analyses were performed to investigate the association between ALDH2*2 and AF occurrence and progression. COX regression analysis was used to explore the association of ALDH2*2 with AF recurrence after catheter ablation. Results: The prevalence of AF differed significantly between the ALDH2*2 group (102/251) and ALDH2*1/*1 group (330/673) (P=0.023). For AF occurrence, in the univariate analysis, alcohol consumption was a risk factors (OR: 1.503, P=0.003), whereas ALDH2*2 was a protective factor (OR: 0.712, P=0.023). In the multivariate analysis, alcohol consumption (P=0.156) and ALDH2*2 (P=0.096) were no longer independent factors. ALDH2*2 with non-drinking was associated with a decreased AF occurrence (OR: 0.65, P=0.021), whereas ALDH2*2 with drinking was not (P=0.365). For AF progression, multivariate analysis revealed ALDH2*2 could promote persistent AF in female AF patients (OR: 2.643, P=0.008). Cox regression analysis suggested that ALDH2*2 (P=0.752) was not a risk factor for AF recurrence after catheter ablation during a median 6 months follow-up. Conclusions: While ALDH2*2 was not directly related to AF, ALDH2*2 with non-drinking was associated with a decreased incidence of AF. ALDH2*2 may accelerate AF progression in female patients, increasing the likelihood of developing persistent AF. Therefore, individuals with ALDH2*2 should refrain from consuming alcohol to decrease the onset and progression of AF.